The Development of Video-Based Learning Media to Support Craft Practice - Rosmala Dewi; Nurbaiti Nurbaiti; Fitriana Fitriana; Febiyani Sakinah (Proceedings of AICS - Social Sciences, 2021)
The learning process in the Design Crafts Course emphasizes on practice learningthrough crafting from the student’s creative design that boast an aesthetic value. TheCOVID-19 pandemic affects the practical learning process, so it requires an appropriatestrategy to support the learning process. This study aims to explain the process andstages of online-based learning video making in the Design Craft Course and to test thefeasibility of the videos. The study falls under the criteria of the RD research (Researchand Development) through the procedural model. The developed video was validatedby a media expert and a material expert before being tested for the fourth semesterstudents of the year 2018and 2019, with 12 students in total. The researchers madeuse of the Likert scale-based questionnaire to collect the data in order to get theresponses from the media expert, the material expert, and the students about the video.A descriptive statistic data analysis was utilized to analyze the obtained data, whichcame in the form of percentages. The results show that the making process of theonline-based learning video met the good category with the percentage of70.83%, based on the results of the media expert test. The result of the material experttest is 89.58% which is very good; and the result of the students’ responses to onlinebasedlearning video in the Design Craft Course is 86.85%, which is in the very goodcategory. From the results, it can be concluded that video-based learning can be appliedfor the fourth semester students of the Design Craft Course at the Family WelfareProgram in the Faculty Teacher Training and Education, Syiah Kuala University. Basedon the results and the conclusions of the research, it is suggested that to increase theeffectiveness of the video-based learning, researchers can carry out face-to-facelearning experiments and evaluations.Keywords: Video-Based Learning, Online-Based Craft Learning